2015
DOI: 10.4136/ambi-agua.1615
|View full text |Cite
|
Sign up to set email alerts
|

Atividades de lactato desidrogenase e malato desidrogenase de Astyanax bimaculatus (lambari) da bacia hidrográfica do rio Una como biomarcadoras de impacto ambiental

Abstract: Fish spend their whole life cycle in water and receive the influence of its physico-chemical and biological components over time. The activities of lactate dehydrogenase (LDH) and malate dehydrogenase (MDH) of aquatic organisms can be altered by pollutants in the water. The aim of this study was to determine whether the activities of LDH and MDH in the gills and liver of Astyanax bimaculatus (lambari do rabo amarelo or Two Spots Astyanax in English), can be used as biomarkers of environmental impact in the Una… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 23 publications
1
7
1
2
Order By: Relevance
“…These results indicate that only SOD was sensible to environmental conditions present in P2. The physicochemical analysis of the water of sites P1, P2 and P3 at the time of fish capture has already been published, as well as the map with the location of these sites (Batista et al, 2014, Ribeiro et al, 2015. These data from the physicochemical analyses indicated that: (1) the less impacted site was P1, although its total phosphate level (0.3 mg L -1 ) was slightly elevated in relation to reference values (0.1 mg L -1 ); (2) the conductivity of the P2 aquatic environment (198.7 S cm -1 ) was 1.9 times higher than in P1, and 1.6 times higher than in P3, showing that P2 fish were exposed to high levels of electrolytes from an impacted environment (CETESB, 2009); (3) P3 presented the highest values of chemical oxygen demand (COD), indicating abundance of organic matter in the water.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These results indicate that only SOD was sensible to environmental conditions present in P2. The physicochemical analysis of the water of sites P1, P2 and P3 at the time of fish capture has already been published, as well as the map with the location of these sites (Batista et al, 2014, Ribeiro et al, 2015. These data from the physicochemical analyses indicated that: (1) the less impacted site was P1, although its total phosphate level (0.3 mg L -1 ) was slightly elevated in relation to reference values (0.1 mg L -1 ); (2) the conductivity of the P2 aquatic environment (198.7 S cm -1 ) was 1.9 times higher than in P1, and 1.6 times higher than in P3, showing that P2 fish were exposed to high levels of electrolytes from an impacted environment (CETESB, 2009); (3) P3 presented the highest values of chemical oxygen demand (COD), indicating abundance of organic matter in the water.…”
Section: Resultsmentioning
confidence: 99%
“…Other suitable biomarkers are MDH from brain because the activity of brain MDH was elevated in fish from P3, as well as muscle MDH in fish from P2 (de Almeida et al, 2016). LDH from gills could also be a biomarker because the activity of gill LDH was lower in fish from P3, in comparison to those of P1 (Ribeiro et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations